40th birthday of the Italian Mental Health Law 180 – perception and reputation abroad, and a personal suggestion. (6th November 2017) - Becker, T.; Fangerau, H.
Abstract : How things are perceived from a distance may help better understand their nature. Perceptions at home are likely to shape perceptions abroad. The mutual cross-references between local and distant perspectives on the Italian Mental Health Law 180 may help understand the process which preceded and resulted in the reform. This editorial argues that Law 180 came about at a unique – enabling – time in history. It argues that the run-up to and passing of Law 180 constituted a great accomplishment by professionals, the wider public and politicians/administrators. This editorial goes on to argue that the profession managed to cope with (many) adverse effects of the reform. The attention that Law 180 has received internationally should be devoted to other national (or regional) mental health reform processes as this may help us to understand how mental health care systems evolve and what defines 'windows of (operative) opportunity' or 'moments for (public) action'.